2021
DOI: 10.3390/antiox10081234
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Biomarkers in the Relationship between Type 2 Diabetes and Air Pollution

Abstract: The incidence and prevalence of type 2 diabetes have increased in the last decades and are expected to further grow in the coming years. Chronic hyperglycemia triggers free radical generation and causes increased oxidative stress, affecting a number of molecular mechanisms and cellular pathways, including the generation of advanced glycation end products, proinflammatory and procoagulant effects, induction of apoptosis, vascular smooth-muscle cell proliferation, endothelial and mitochondrial dysfunction, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 106 publications
0
8
0
Order By: Relevance
“…In addition to oxidative stress and neutrophilic inflammation, PM exposure has been associated with activation of the coagulation and fibrinolytic system [119,120]. Cascio et al [121] found, in a mouse model, that after exposure to ultrafine particulate matter (UFP) there was an increase in the platelets, plasma fibrinogen, and soluble P-selectin levels, with reduced bleeding time, implying an increased thrombogenic potential.…”
Section: Human Primary Neutrophils Murine Primary Neutrophilsmentioning
confidence: 99%
“…In addition to oxidative stress and neutrophilic inflammation, PM exposure has been associated with activation of the coagulation and fibrinolytic system [119,120]. Cascio et al [121] found, in a mouse model, that after exposure to ultrafine particulate matter (UFP) there was an increase in the platelets, plasma fibrinogen, and soluble P-selectin levels, with reduced bleeding time, implying an increased thrombogenic potential.…”
Section: Human Primary Neutrophils Murine Primary Neutrophilsmentioning
confidence: 99%
“…For instance, PM 2.5 alters levels of oxidative stress biomarkers in mice including glutathione peroxidase and malonic dialdehyde (73). Research has identified oxidative stress as one potential feature underlying the toxic effect of air pollution, which activates NF-kB translocation into the nucleus and causes an inflammatory response and cytokine production (74)(75)(76)(77). Meanwhile, air pollution can produce pro-inflammatory mediators, including highly sensitive C-Reactive Protein, TNFa, IL-1b, IL-6 and IL-8, resulting in local or systemic inflammation (8,78,79).…”
Section: The Potential Relationship Between Air Pollution and Gdmmentioning
confidence: 99%
“…Automotive vehicular traffic is a prevalent source of air pollution, especially in cities. In animal studies, traffic-related air pollution (TRAP) was shown to elicit oxidative stress and subclinical inflammation, resulting in impaired insulin signaling and insulin resistance [ 9 ]. The sole systematic review to date evaluating the association of TRAP exposure with diabetes concluded there was a positive association between the two [ 10 ].…”
Section: Introductionmentioning
confidence: 99%